'It's nice to just be you': The influence of the employment experiences of UK military spouses during accompanied postings on well-being. Issue 1 (March 2019) - Gribble, Rachael; Goodwin, Laura; Oram, Sian; Fear, Nicola T
Repeated military relocations (accompanied postings) can have a detrimental effect on employment and well-being among the spouses and partners of military personnel. Semi-structured telephone interviews were conducted with 19 spouses of British Army/Royal Air Force personnel with recent experience of accompanied postings to explore this issue through the lens of self-determination theory; all were married women with at least one child. Participants explained how employment contributed to an independent identity, enabling social connectedness, providing a sense of self-confidence and value but limiting agency over employment decisions. Spouse employment, and therefore, well-being could be improved by the provision of better childcare access or additional support in finding employment and training opportunities.